Reducing the Incidence of Low Birth Weight in Low-Income Countries Has Substantial Economic Benefits - Alderman, Harold; Behrman, Jere R. (Oxford University Press on behalf of the World Bank, 2013)
Reducing the incidence of low birth weight not only lowers infant mortality rates but also has multiple benefits over the life cycle. This study estimates the economic benefits of reducing the incidence of low birth weight in low-income countries, both through lower mortality rates and medical costs and through increased learning and productivity. The estimated economic benefits, under plausible assumptions, are fairly substantial, at about $510 per infant moved from a low-birth-weight status. The estimated gains are primarily from increases in labor productivity (partially through more education) and secondarily from avoiding costs due to infant illness and death. Thus there may be many interventions to reduce the incidence of low birth weight that are warranted purely on the grounds of saving resources or increasing productivity.